Aplikasi Data Pelanggan Berbasis Java dan Mobile pada PT. PLN (Persero) Area Semarang - Rizaldi Habibie; R. Rizal Isnanto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2016)
In modern times, like today, the role of software or applications that run on top of the platform is very important. This is because almost all of the work done by the people, made by the software or application. Applications can be used to assist in the processing of data and upload the final report. Data recorded previously processed by the paper can be recorded and processed by the application so that more efficiently. PT. PLN (Persero) Semarang District State electricity company has many customers in the city of Semarang. Customer data belonging to this company has not been processed in digital form. This causes the data of regular visits undertaken are not directly connected with customer data, owned so inefficient and requires a long process in the course of the report. Thus, it takes an application that can help in the treatment of customer data, data of visited consumer, and generate reports . Customer data Java-based and mobile applications for PLN (Persero) Semarang District State intended for the treatment of customer data, data of visited connsumer and generate reports. The application consists of two application. The first applications developed using the programming language Java, which can run on the operating system Windows. The second application was designed and implemented using the framework ionic, which can run on the Android operating system. This application uses MySQL as a database management system, which is used for data storage media.